METAFORA BUNGA DALAM MASYARAKAT JEPANG - Rahman, Abi Bur; Aibonotika, Arza; Isnaini, Zuli Laili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study discusses the kotowaza and kanyouku with elements of flowers, especially cherry blossoms, roses, and lotus which have metaphorical meanings in Japanese society. This research is a qualitative descriptive study using Lakoff and Johnson's figurative theory with cognitive linguistic approach. The background to this research is difficulty understanding the relationship between the meaning of kotowaza and kanyouku to individuals outside of their speaking communities because cultural differences background from the formation of the kotowaza and kanyouku. The study aims is to know the kotowaza and kanyouku with elements of flowers and their metaphorical meanings. As the results, from 12 data consisting of 9 kotowaza and 3 kanyouku found 6 structural metaphors and 6 ontological metaphors. Then based on the content (naiyo), the discovery of 1 Jinsei no oshie, shinri o arawashita, 5 Seikatsu no chisiki, chie o tataite wataru, and 1 Hito o hihan shitari hinikuttari shita mono, and 2 Monogoto no yoosu omoshiroku tatoeta mono. The metaphorical meaning found in kanyouku refers to food, beauty, and positive character.Key Words: metaphor, flower, kotowaza, kanyouku, cognitive linguistics